Proteomic analysis of human adipose tissue after rosiglitazone treatment shows coordinated changes to promote glucose uptake. - Ahmed, M; Neville, M; Edelmann, M; Kessler, B; Karpe, F (2010)
The aim of this study was to identify potential protein targets for insulin sensitization in human adipose tissue using unbiased proteomic approaches. Ten moderately obese, but otherwise healthy, subjects were treated with rosiglitazone 4 mg b.i.d. for 14 days and global protein and gene expression changes were monitored. Proteomic analysis revealed distinct up- or downregulation (greater than twofold) in 187 protein spots on the two-dimensional (2-D) gel images between day 0 and day 1 adipose tissue samples. When comparing the protein spots on the gels from day 0 with that of 14-day-treated samples, 122 spots showed differential expression. There was a striking increase in the expression of proteins involved in glucose transporter-4 (GLUT4) granule transport and fusion (actin, myosin-9, tubulin, vimentin, annexins, moesin, LIM, and SH3 domain protein-1), signaling (calmodulin, guanine nucleotide-binding proteins), redox regulation (superoxide dismutase, catalase, ferritin, transferrin, heat shock proteins), and adipogenesis (collagens, galectin-1, nidogen-1, laminin, lamin A/C). However, there was an intriguing absence of correlated changes in mRNA expression, suggesting adaptation at a post-transcriptional level in response to rosiglitazone. Thus, the major changes observed were among proteins involved in cytoskeletal rearrangement, insulin and calcium signaling, and inflammatory and redox signals that decisively upregulate GLUT4 granule trafficking in human adipose tissue. Such orchestrated changes in expression of multiple proteins provide insights into the mechanism underlying the increased efficiency in glucose uptake and improvement of insulin sensitivity in response to rosiglitazone treatment.